PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPERCAYAAN DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL MEDIASI - Rahma Pratiwi Saragih, Lamidi & Setyaningsih Sri Utami (Universitas Slamet Riyadi, 2017)
The purpose of this study are: 1) To analyze significant influence product quality and service quality on customer satisfaction. 2) To analyze significant influence product quality, service quality and customer satisfaction to customer confidence. 3) To analyze significant influence product quality and service quality to customer confidence mediated by customer satisfaction. The research method used survey method, the type of data used quantitative and qualitative data, the data source used primary data and secondary data. The population in this study is the Business Partner Customer Savings Bank Mandiri Branch Colomadu Karanganyar creating new accounts or new accounts in the period April 2015 s / d April 2016 as many as 700 customers. The number of samples in this study were 70 respondents, the sampling technique uses accidental sampling. Data collection methods used: questionnaire, observation and documentation. Data analysis technique used to test the validity, reliability test, classic assumption test, path analysis. Based on the results obtained conclusions: 1) There is significant influence product quality and service quality on customer satisfaction. 2) There is significant influence product quality, service quality and customer satisfaction to customer confidence. 3) Customer satisfaction mediates the effect of product quality and service quality to customer confidence.Keywords: product quality, service quality, customer satisfaction, customer confidence.